Praktek Penanaman Nilai Toleransi Bagi Remaja Di Lingkungan Masyarakat Multikultural Rw 04 Kelurahan Ciwalen Garut Perspektif Ilmu Pendidikan Islam - Maria, Anly; Nurdiani, Elda (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Tolerance among adolescents in a multicultural society is essential. In today's diverse world, young people must embody specific values of tolerance, especially within a multicultural community. From the perspective of Islamic Education, tolerance carries particular significance, and issues of multiculturalism have been addressed historically since the time of the Prophet Muhammad (SAW). This study aims to understand and describe: (1) the profile of the multicultural community in RW 04, Ciwalen Subdistrict, Garut; (2) the attitudes and practices of instilling values of tolerance among adolescents within this multicultural community; (3) the practices of instilling tolerance values for adolescents in the multicultural environment of RW 04, Ciwalen Subdistrict, Garut, from the perspective of Islamic Education. This research explores the phenomena or practices of inculcating tolerance values among adolescents in RW 04, Ciwalen Subdistrict, Garut, and examines these practices through the lens of Islamic Education. The research employs a qualitative descriptive method. The primary data sources include observations, interviews, and documentation. Secondary data sources comprise books and other references, especially the Qur'an and Hadith, relevant to this study. Data processing in this research follows qualitative analysis principles, including data reduction, data presentation, and drawing conclusions. The findings indicate that the practice of instilling tolerance values among adolescents in the multicultural community of RW 04, Ciwalen Subdistrict, Garut, is conducted in a manner characterized by peace, harmony, simplicity, unity, tolerance, and coexistence. These practices align with the values of tolerance and the essence of multicultural life in accordance with Islamic Education. Keywords: Tolerance Values for Adolescents, Multicultural Society, Islamic Education